Effects of feeding outer bran fraction of rice on lipid accumulation and fecal excretion in rats. Issue 8 (3rd August 2015) - Ijiri, Daichi; Nojima, Tsutomu; Kawaguchi, Mana; Yamauchi, Yoko; Fujita, Yoshikazu; Ijiri, Satoru; Ohtsuka, Akira
Abstract: Outer bran fraction of rice (OBFR) contains higher concentrations of crude fiber, γ-oryzanol, and phytic acid compared to whole rice bran (WRB). In this study, we examined the effects of feeding OBFR on lipid accumulation and fecal excretion in rats. Twenty-one male rats at seven-week-old were divided into a control group and two treatment groups. The control group was fed a control diet, and the treatment groups were fed OBFR- or WRB-containing diet for 21 days. There was no significant difference in growth performance. Feeding OBFR diet increased fecal number and weight accompanied by increased fecal lipid content, while it did not affect mRNA expressions encoding lipid metabolism-related protein in liver. In addition, feeding OBFR-diet decreased the abdominal fat tissue weight and improved plasma lipid profiles, while WRB-containing diet did not affect them. These results suggested that feeding OBFR-diet might prevent lipid accumulation via enhancing fecal lipid excretion in rats. Graphical abstract: : A, Excreted feces from a rat per day. B, Fecal weight from a rat per day. C, The weight of the abdominal fat tissue. D, Plasma triacylglycerol level. Values are expressed as mean ± SEM ( n = 7). OBFR; outer bran fraction of rice, WRB; rice bran.